Analysis of Fishermen’s Unwelfare Problems in the City of Tanjungbalai Based on the Maqashid Sharia Approach (Case Study of Fishermen in Tanjungbalai) - Iman Purdani; Imsar Imsar; Rahmat Daim Harahap (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to analyze the factors that cause fishermen’s welfare in the city of Tanjung Balai, as well as provide solutions that can be implemented by the government and society in improving the welfare of fishermen based on the Maqashid Sharia approach. This research was conducted through a qualitative approach with data collection techniques through interviews and document studies. The results showed that the factors causing the welfare of fishermen in Tanjung Balai include the lack of government policy support in managing fishery resources, the low level of education and skills of fishermen, the problem of limited market access, and environmental conditions that are not conducive to the sustainability of fisheries. The Maqashid Sharia approach is used to analyze this problem by taking into account the objectives of Islamic Sharia. In the context of fishermen in Tanjung Balai, the Maqashid Sharia approach can provide holistic and sustainable solutions by taking into account the welfare of fishermen in the physical, social, economic, and spiritual aspects. This research shows that the welfare of fishermen in Tanjung Balai is a complex problem and requires a holistic and integrated solution. Therefore, efforts from the government and society are needed to improve the welfare of fishermen by taking into account the objectives of Maqashid Sharia. Implementation of this approach is expected to have a positive impact on the welfare of fishermen and society in general.